Purification of the Porcine Platelet GP IIb-IIIa Complex and the Propolypeptide of von Willebrand Factor - Royo, Teresa; Vidal, Matilde; Badimon, Lina (Thrombosis and Haemostasis, 1998)
Platelet membrane glycoproteins (GP) are involved in platelet adhesion and aggregation. The glycoprotein IIb-IIIa complex (GP IIbIIIa) is a Ca2+-dependent heterodimer that binds fibrinogen and other adhesive proteins, thereby mediating platelet aggregation and adhesion. We have purified two major glycoproteins from pig platelets by Concanavalin A-Sepharose, Heparin-Sepharose and Sephacryl S-300 HR chromatography (Fitzgerald et al. Anal Biochem, 1985): i) the GP IIb-IIIa complex, GP IIb Mr = 140,000 and GP IIIa a single chain of Mr = 95,000-100,000; and ii) a predominant glycoprotein of high molecular weight, the propolypeptide of von Willebrand factor (Mr = 80,000-100,000). Western-blot analysis of the purified GP IIb-IIIa showed that only certain monoclonal antibodies against the human receptor specifically recognize the porcine complex. Differences between the porcine and human GP IIb-IIIa glycoproteins could partially explain the decreased inhibitory effects of GP IIb/IIIa-antagonists (against the human receptor) in porcine platelets.